Pengaruh gaya kepemimpinan dan motivasi kerja terhadap kinerja karyawan - Amalia, Syarah Fatimah; Slamet, Turah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The purpose of this research is to analyze how different types of leadership and levels of workplace motivation affect employee productivity at PT Permodalan Nasional Madani's Jonggol Branches 1 and 2. This study makes use of a quantitative approach to research. Employees at PNM Jonggol Branch 1&2 were given questionnaires to fill out as part of the data collection procedure. Multiple linear regression analysis was used to assess the study's hypothesis. According to the results, a leader's approach to managing personnel has a significant and beneficial effect on productivity. Employee productivity at PNM Jonggol Branch 1&2 increases in direct proportion to the leader's skill in fostering an enabling work environment. The current research also showed that work motivation has a significant positive effect on productivity. The productivity of workers at PNM Jonggol Branch 1 and 2 rises in tandem with the company's efforts to inspire them to do their best. Furthermore, the results showed that the impact of leadership style and job motivation together was substantial. Leadership that inspires and motivates employees can have a significant impact on productivity in the workplace.